(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
Study seeks to try to extrapolate and predict reality and specifications of the historical evolutionary phase that will come after the current phase of globalization. It ranks among the studies of future studies or philosophy of history. Where the study found that the world after globalization will be directed automatically, whether consciously of it or no awareness about market of free competition, but it certainly will not reach it certainly contraindications process known about this market, but it will reach at least to the market, monopolistic competition and close to free competition, between the countries of the world Advanced Currently, the world’s growing after provided, a situation identical to the most important principles and assumptions of the Islamic economic system, but without being followed by a necessarily check the rest of the principles and assumptions of this system, as well as the vast difference between the capitalist system positive, and the Islamic regime derived its origins from Almighty God, especially in Raitema philosophical world, the system first physical in nature, while the second believes that the two sides of the human material is organic in composition, and the other is spiritual not physical.